Eco-friendly automotive disc brake and cylinder liner (Eco SiC) - Maleque, Md. Abdul; Paijan, Lailatul Harina; Abdul Rahman, Nurfarina (2017)
The products focus on development of eco-friendly SiC for automotive disc brake and cylinder liner. This new eco-SiC will be used to replace the conventional component which is made up of metallic grey cast iron for disc brake and surface coating for surface modification for cylinder liner. The brake disc is installed and connected to the wheel and the axle. Friction causes the disc and attached wheel to slow or stop the vehicle. Thus, the disc brake is one of the most important features in the vehicle because it involves the safety factor. The current problem of disc brake is bulky and heavy that require more energy and fuel consumption. The production process requires high energy, time and emits CO2 gas that contributes to air pollution. The lower thermal conductivity of cast iron leads to the non-uniform distribution of heat on the surface during sliding with the brake pad. The recyclability of the cast iron is advantageous but the evolution of CO2 during re-melting has to be taken into consideration. A cylinder liner is a cylindrical part to be fitted into an engine block to form a cylinder. It is one of the most important functional parts to make up the interior of an engine. This part functioned as the inner wall of a cylinder, forms a sliding surface for the piston rings while retaining the lubricant within. The most important function of cylinder liner is the excellent characteristic as sliding surface. It receives combustion heat through the piston and piston rings and transmits the heat to the coolant. A cylinder wall in an engine is under high temperature and high pressure, with the piston and piston rings sliding at high speeds. Due to this extreme condition, the surface modification is required to improve the hardness and wear resistance of this component. This modification can be done by changing the surface layer without affecting the bulk properties of the material. Many surface treatment such as nitriding, laser technique and ion implantation successfully used to improve the surface properties. However, all these processes are expensive and take long period. Therefore, new development of the surface modification for cylinder liner is required to explore the possibility of producing eco SiC resolidified layer on the surface by TIG torch melting process with simple and low cost techniques. The synthetic SiC material has a high temperature endurance property which makes it more stable performance at high temperature. However, the price of the synthetic SiC reinforcing agent itself is very expensive although it offers better mechanical properties performance. Therefore, the aim is to synthesise ecofriendly SiC reinforcement material from the agricultural waste rice husk using simple and cost effective pyrolysis process. The eco-SiC will be used as new product to manufacture the eco-friendly disc brake and surface engineered cylinder liner. The characterization and performance of the products will be performed using scanning electron microscope, hardness test, x-ray diffraction, differential scanning calorimetry, tribo-meter, fatigue and high temperature test and field assessment test. It is expected that the eco-friendly disc brake would be suitable for the replacement of the existing cast iron material without sacrificing performance properties with better performance in terms of light weight, energy saving, eco-friendly and waste to wealth. For cylinder liner, it is expected that the new surface modification would have a hard surface layer, high wear resistance, costefficient and eco-friendly. The product development activities will take about 2.5 years. It will start with concept and design review takes about 4 months, manufacturing setup for 3 months, fabrication and development process for 7 months, verification and validation test for 15 months and pilot plan development for 5 months. The marketing strategy to promote this product is using media such as Facebook, Instagram, radio or motor trader magazine. The technical seminar also proposed to give awareness and educate people the importance of eco-friendly product in the vehicle and benefits of using it. Total expenditures to manufacture this product is ~ RM 350,000. Based on the statement of cash flows, the investment can be paid back within 5 years. The cost model analysis showed that the estimation cost to produce 1 unit eco-SiC disc brake is RM 128 and surface engineered cylinder liner is RM 28 for sample size of 30 x 50 mm. The calculation includes raw materials cost and labour charge. The supply chain route starts with raw materials to the material supplier. Then, the vendor will manufacture the finish product into eco-friendly disc brake and cylinder liner. All the finish products will be distributed by appointed distributor to 2 automotive big maker in Malaysia, Proton and Perodua. Compared with commercial products, the eco-friendly product are better properties in terms of less weight, less cost, less material usage, eco-friendly, better performance and high sustainability. To setup this project, the management team with high skilled people is needed to manage and run the project smoothly. The organisation chart consists of managing director, production; quality and marketing team are required to strengthen the team.